Binding of Human Platelet Glycoprotein lb and Actin to Fragments of Actin-Binding Protein - Aakhus, Anne M; Wilkinson, J Michael; Solum, Nils Olav (Thrombosis and Haemostasis, 1992)
Actin-binding protein (ABP) is degraded into fragments of 190 and 90 kDa by calpain. A monoclonal antibody (MAb TI10) against the 90 kDa fragment of ABP coprecipitated with the glycoprotein lb (GP lb) peak observed on crossed immunoelectrophoresis of Triton X-100 extracts of platelets prepared without calpain inhibitors. MAb PM6/317 against the 190 kDa fragment was not coprecipitated with the GP lb peak under such conditions. The 90 kDa fragment was adsorbed on protein A agarose from extracts that had been preincubated with antibodies to GP lb. This supports the idea that the GP Ib-ABP interaction resides in the 90 kDa region of ABP. GP lb was sedimented with the Triton-insoluble actin filaments in trace amounts only, and only after high speed centrifugation (100,000 × g, 3 h). Both the 190 kDa and the 90 kDa fragments of ABP were sedimented with the Triton-insoluble actin filaments.